EDUCATION AND ERGONOMIC EXERCISE TRAINING FOR PATIENTS WITH HYPERTENSION IN THE WORKING AREA OF TENAYAN RAYA PUBLIC HEALTH CENTER PEKANBARU - Dewi Sartika (PITIMAS: Journal of Community Engagement in Health, 2026)
Hypertension is one of the most prevalent non-communicable diseases and a major risk factor for cardiovascular disease. The management of hypertension involves not only pharmacological therapy but also health education and appropriate physical activity, one of which is ergonomic exercise. This community service program aimed to improve the knowledge and skills of older adults with hypertension in performing ergonomic exercise in the working area of Tenayan Raya Public Health Center, Pekanbaru. The target participants of this program were four older adults with hypertension. The program was conducted using personalized health education and demonstration methods, accompanied by the community service team. The participants' skills were evaluated through direct observation of their ability to perform ergonomic exercise correctly. The results showed that all four participants were able to perform the ergonomic exercise movements properly after the training. In conclusion, this community service program improved the knowledge and skills of older adults with hypertension in performing ergonomic exercise as a non-pharmacological approach to support hypertension management. This program is expected to be implemented continuously as a promotive and preventive strategy to improve the quality of life of patients with hypertension.